Dynamics of current induced magnetic superstructures in exchange-spring devices: Магнетизм - Kadigrobov, A.M.; Shekhter, R.I.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Thermoelectric manipulation of the magnetization of a magnetic layered stack in which a low-Curie temperaturemagnet is sandwiched between two strong magnets (exchange spring device) is considered. Controllable Joule heating produced by a current flowing in the plane of the magnetic stack (CIP configuration) induces a spatial magnetic and thermal structure along the current flow — a magnetothermal-electric domain (soliton). We show that such a structure can experience oscillatory in time dynamics if the magnetic stack is incorporated into an electric circuit in series with an inductor. The excitation of these magnetothermionic oscillations followthe scenario either of “soft” of “hard” instability: in the latter case oscillations arise if the initial perturbation is large enough. The frequency of the temporal oscillations is of the order of 105–107 s–1 for current densities j ~ 106–107 A/cm2.